Why Walking the Common is more than a Walk in the Park - Romano , Nike; Mitchell , Veronica; Bozalek , Vivienne (Journal of Public Pedagogies, 2019)
For the past few years, as concerned academics and educators in South African higher education, we have come together to meet/think/drink coffee/eat/discuss our research and teaching practices in a coffee shop that overlooks the Rondebosch Common, a public space and national heritage site. The Common invited us to take our thoughts for a walk and we embarked on numerous walking encounters that affected and troubled us in many ways. Our walks became research-creation events that surfaced the implicatedness of our white settler privilege. As we grappled with the complexities and ambivalences grounded in our relationality with this contested site, we were prompted to explore hauntology as a theoretical orientation for our pedagogical practices. Walking with/through the demarcated land that is surrounded by privilege in terms of buildings, services and residences enacted and materialised entanglements of the past/present/future histories. We felt an exchange of affect between those present, the ghosts of colonial and apartheid histories, and the implications for our ongoing teaching. Following Haraway's (2016) ‘staying with the trouble’ and Tsing et al.'s (2017) ‘how to live on a damaged planet’, the relationships between human and non-human continue to haunt us, as we grapple with the im/possibility of finding common ground in a country devastated by colonial and apartheid violences.